Conditions for placing foodstuffs for human consumption according to executive decree N° 17-140 of April 11th, 2017.. - Djari, Roukia; Kalou, Hicham (Journal of Human Sciences, 2021)
The recent and rapid developments in the field of food at all stages of the food chain have made attention to consumer protection based on assessing and managing risks in food, whether the sources of risk are biological, chemical or natural, therefore, the Algerian legislator and like other legislators has set conditions for hygiene and hygiene of foodstuffs during the process of placing them for human consumption through Executive Decree No. 17-140, where by food facilities are required to ensure the hygiene and safety of foodstuffs based on the principles of the Hazard Analysis and Critical Control Points (HACCP) system